Are workers in construction sites of Mangalore city healthy? a cross-sectional study - Raj, Utsav; R., Pracheth; K. R., Nischith (International Journal Of Community Medicine And Public Health, 2018)
Background: Construction site workers are prone to develop health problems due to poor living conditions. This is magnified by lack of timely access to health care. Thus, we sought to explore the health status of construction site workers. Methods: A cross sectional study was conducted in construction sites located in an urban area of Mangalore, from September to November, 2015 among workers aged ≥18 years, with consent. Information was obtained through a pre-designed, pre-tested interview schedule. Results: A total of 178 individuals participated in the study, which included 160 (89.80%) males. Majority, (80.80%), stated that they had experienced fever at least once in the past one year. Other major complaints were blocked nose (17.40%), followed by skin diseases (12.70%) and cough which was present in 12.30%. When the study participants had an illness, 65.70% visited a health facility. Majority (82.50%) preferred private doctors, 62.50% visited the doctor so that they could work better and earn more, and 37.0% were unable to afford the treatment due to high treatment cost. Conclusions: The most common health complaint was found to be fever. Nearly half of the study participants had illness which required treatment in the last one year. More than half visited a health facility when ill. A high proportion (82.50%) preferred private health facility.